Are previous episodes of bacterial vaginosis a predictor for vaginal symptoms in breast cancer patients treated with aromatase inhibitors?. Issue 2 (June 2018) - Gade, Malene R; Goukasian, Irina; Panduro, Nathalie; Kamby, Claus; Nilas, Lisbeth; Tuxen, Malgorzata K; Bjerrum, Lars
Objective: To estimate the prevalence of vaginal symptoms in postmenopausal women with breast cancer exposed to aromatase inhibitors, and to investigate if the risk of vaginal symptoms is associated with previous episodes of bacterial vaginosis. Methods: Patients from Rigshospitalet and Herlev University Hospital, Denmark, were identified through the register of Danish Breast Cancer Cooperation Group and 78 patients participated in the study. Semiquantitave questionnaires and telephone interview were used to assess the prevalence of vaginal symptoms and previous episode(s) of bacterial vaginosis. Multivariable logistic regression models were used to assess the association between vaginal symptoms and previous episodes of bacterial vaginosis. Results: Moderate to severe symptoms due to vaginal itching/irritation were experienced by 6.4% (95% CI: 2.8–14.1%), vaginal dryness by 28.4% (95% CI: 19.4–39.5%), and dyspareunia by 23.1% (95% CI: 11.0–42.1%). Patients with earlier episodes of bacterial vaginosis had an increased risk of vaginal dryness when exposed to a treatment with an aromatase inhibitor, adjusted OR 5.5 (95% CI 1.3–21.6). Conclusion: A considerable number of patients exposed to aromatase inhibitor have vaginal symptoms and the risk is highest among patients with earlier episodes of bacterial vaginosis.